Bioavailability of phosphorus in granulated and pyrolyzed broiler manure - Sarvi, Minna; Hagner, Marleena; Velmala, Sannakajsa; Soinne, Helena; Uusitalo, Risto; Keskinen, Riikka; Ylivainio, Kari; Kaseva, Janne; Rasa, Kimmo (Elsevier, 2021)
Production of organic fertilizers from poultry manure may compromise availability of phosphorus (P) to plants. This study examined the effects of granulation, feather meal addition, and pyrolysis on bioavailability of P in broiler manure in a pot experiment with ryegrass and assessed whether P availability is enhanced by inoculating arbuscular mycorrhizal fungi (AMF) into soil. Granulated broiler manure gave similar plant yield and P uptake to superphosphate. Feather meal addition had a minor negative effect on P availability, whereas pyrolysis lowered the fertilization effect of broiler manure. The yield-based mineral-P equivalences were 120%, 85% and 75% during the first harvest, and 100%, 75% and 45% during one growing season for granulated unamended, granulated amended with feather meal and pyrolyzed broiler manure. Soil inoculation with AMF did not enhance P availability. Granulated poultry manure is suitable as a P fertilizer for annual crops with comparable bioavailability to mineral fertilizer P, whereas pyrolyzed poultry manure is suitable as a slow-release or storage P fertilizer in slightly acidic soils. Knowledge on P bioavailability in organic fertilizers produced with different technologies can be used for optimizing fertilization, minimizing build-up of soil P and its adverse environmental effects.
Keywords: Poultry litter; Biochar; Slow pyrolysis; Granulation; Organic fertilizer; Arbuscular mycorrhizal fungi